Sandflies (Diptera: Psychodidae: Phlebotominae) collected on the banks of the Velhas River in the state of Minas Gerais, Brazil - Lara Saraiva; Gustavo Mayr de Lima Carvalho; Cristiani de Castilho Sanguinette; Deborah Aparecida Alves de Carvalho; Alda Lima Falcão; José Dilermando Andrade Filho (Memorias do Instituto Oswaldo Cruz, 2008)
Leishmaniases are endemic to several Brazilian states, including Minas Gerais. As many cases of these diseases are diagnosed in Minas Gerais every year, this paper aimed to determine the diversity of the species of sandflies vector of leishmaniases, in Lassance and Corinto on the banks of the Velhas River. Over two years, 21,014 specimens of sandflies, belonging to 19 species were captured with light traps. Of these specimens, Nyssomyia neivai (Pinto 1926) (84.18%), Nyssomyia intermedia (Lutz & Neiva 1912) (13.41%), Evandromyia lenti(Mangabeira 1938) (0.99%) and Evandromyia sallesi (Galvão & Coutinho 1939) (0.48%) were the most represented. The former two species could be involved in the epidemiological chain of leishmaniasis in this region. No significant difference was found between the species compositions on the two river banks.